Prithvi Narayan Shah and Postcolonial Resistance - Kafle, Hem Raj (Bodhi: An Interdisciplinary Journal, 2010)
Nepalese monarchy fell under an inextricable political array after April 2006 as the country took radical directions in the hands of political parties. First, the reinstated parliament declared the country secular in June 2006, which undermined the religious-political significance attributed to Hindu kings. Second, the Maoists successively signed the Comprehensive Peace Accord with the government (November, 2006), and joined the parliament (January, 2007) and the coalition government (March, 2007). Third, the first historic constituent assembly elections took place (April, 2008). Then the constituent assembly declared the country a republic and formally abolished the monarchy (May, 2008). In other words, a collective upsurge of April 2006, which had started to fight monarchy, ended up abolishing in two years. Thereafter the country headed towards a new phase of history with a collective political thrust for restructuration into a federal republic. DOI: 10.3126/bodhi.v2i1.2867 Bodhi Vol.2(1) 2008 p.136-147